Inspiration in the light of ecological systems and their applications in industrial products (Journal of the College of Basic Education, 2025)
The research addresses the topic of the research (Inspiration in the light of ecological systems and their applications in industrial products) The importance of the research comes from the fact that the process of inspiration from nature, Bio-inspiration, through ecological systems helped the designer in creating ideas to solve the problems facing him at the present time and that have come to meet the needs and inclinations of society.Through this, the goal of the research was identified, which is to identify cases of inspiration according to ecological systems through their actual applications that were extracted in the industrial product and to benefit from simulating the environmental forms that exist around us, in order to enable us to reach design foundations in order to achieve effective integration in the functional and formal performance of the product. Industrial, and the research sample was on devices available at Samsung for the years 2021 - 2022The research consists of five chapters, the first chapter of which deals with the research problem, its importance, objectives, and limits to the research topic. The research problem is embodied in the following: about the relationship between the industrial designer and inspiration from nature in light of Eco-Loge systems, which are related to the behavior of organisms, and the human desire to... All new and innovative products or services within the ecosystems in which they will be used, and it is necessary and inevitable to harmonize these innovations with the environment and preserve it, at least if it is not possible to improve it.The second chapter included two sections for the theoretical framework. The first section included concepts of inspiration from nature, and the second section dealt with ecosystems and their concept. The third chapter was the research methodology, the fourth chapter analyzed the research sample of three industrial products, and the fifth chapter showed several results and conclusions. The most important results of the research were:A concept has been reached to establish a scientific principle upon which the designer relies in order to develop contemporary concepts for elements that have a meaning related to ecological systems.The clarity of the design elements, which were shown in a clear and complementary manner with the surrounding environment and its nature, and that the basic meaning of its elements is to reach the minimum level to achieve functional comfort for humans and satisfy their desires.It is possible to exploit smart material instead of traditional material in product design, helping the designer to easily imitate the shapes of nature according to ecological systems in order to develop the functional performance and aesthetic appearance of the product.